2022
DOI: 10.1021/acs.jmedchem.2c00047
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Enhancer of Zeste Homolog 2 for the Treatment of Hematological Malignancies and Solid Tumors: Candidate Structure–Activity Relationships Insights and Evolution Prospects

Abstract: Enhancer of zeste homolog 2 (EZH2) is a histone methyltransferase that can change the expression of downstream target genes by catalyzing the trimethylation of lysine 27 of histone H3 (H3K27me3). Studies have found that EZH2 is highly expressed in a variety of tumor tissues and is closely related to the occurrence, development, invasion, and metastasis of tumors; therefore, EZH2 is becoming a new molecular target in antitumor therapy. Tazemetostat (EPZ-6438) was approved in 2020 as the first inhibitor targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…3-13 ). Signals of gene repression include repressive histone modifications (e.g., H3K27me3) and loss of methylation (indicating binding and activation) in regions associated with binding of proteins that deposit repressive histone modifications (e.g., polycomb repressive complex components EZH2 65 and SUZ12 66 ) or remove activating histone modifications (e.g., SMARCA4, a component of the SWI/SNF chromatin remodeling complex 67 , which recruits histone deacetylase repressor complexes 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…3-13 ). Signals of gene repression include repressive histone modifications (e.g., H3K27me3) and loss of methylation (indicating binding and activation) in regions associated with binding of proteins that deposit repressive histone modifications (e.g., polycomb repressive complex components EZH2 65 and SUZ12 66 ) or remove activating histone modifications (e.g., SMARCA4, a component of the SWI/SNF chromatin remodeling complex 67 , which recruits histone deacetylase repressor complexes 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…A look back at the history of drug discovery and development reveals that the development of TKIs also faced the above-mentioned three challenges in the early stage. To overcome these challenges, targeted covalent inhibition has been applied in the development of potent and selective TKIs, resulting in 8 approved covalent TKIs (Afatinib, Ibrutinib, Osimertinib, Acalabrutinib, Dacomitinib, Neratinib, Zanubrutinib, and Futibatinib) (18). To a solution of methyl 2-methyl-5-nitrobenzoate (17, 25.00 g, 128.09 mmol) in concentrated H 2 SO 4 was added NBS (27.00 g, 151.70 mmol).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The enhancer of zeste homologue 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2 (PRC2), which catalyzes the transfer of one to three methyl groups from the cofactor S-adenosylmethionine (SAM) to the ε-NH 2 group of H3 lysine 27 (H3K27), resulting in three different methylation states of H3K27 (mono-, di-, or trimethylation of H3K27). , Among others, trimethylation of H3K27 (H3K27me3) contributes to the modification of the chromatin structure, resulting in the repression of gene transcription that promotes differentiation and restrains proliferation in normal cells . Overexpression of EZH2 has been observed in multiple solid and malignant tumors, including tumors of prostate, breast, kidneys, and lungs, myeloma, and leukemia, and its expression level often correlates with disease progression and poor prognosis. Additionally, activating point mutations in the catalytic SET domain of EZH2, such as Y641N, Y641F, and A677G, have been identified in diffuse large B-cell lymphoma (DLBCL) and follicular lymphoma (FL). , Collectively, EZH2 has attracted increasing attention as an attractive anticancer target in the past decade. …”
Section: Introductionmentioning
confidence: 99%
“… 14 H3K27me3 demethylation and trimethylation are primarily catalyzed by the 2 members of the KDM6 family of lysine demethylases (UTX, also known as KDM6A, and JMJD3, also known as KDM6B), and the polycomb complex 2 (PRC2) of lysine methyltransferases. 15 17 Notably, the methylation regulation of H3K27me3 (both demethylation and trimethylation) is involved in cellular transformation and cancer cell plasticity, 14 , 18 and several reports have indicated that PRC2, KDM6A, and KDM6B participate in tumor growth. 19 – 21 Thus, strategies targeting the regulation of H3K27me3 are especially important for cancer treatment.…”
mentioning
confidence: 99%